2014
DOI: 10.1177/0017896914523152
|View full text |Cite
|
Sign up to set email alerts
|

FIFA 11 for Health programme: Implementation in five countries in Sub-Saharan Africa

Abstract: Objective: To assess the effectiveness of the FIFA 11 for Health programme in increasing children's knowledge about communicable and non-communicable diseases in five countries of Sub-Saharan Africa. Method: A prospective five-cohort study was implemented in schools in Ghana (17), Malawi (12), Namibia (11), Tanzania (18) and Zambia (11). The programme consisted of eleven 90-minute sessions consisting of two 45-minute halves of Play Football (football skills) and Play Fair (health issues). Participants were boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Although the authors of several studies acknowledged this as a limitation, they explained that randomizing participants was not always logistically possible and adjusted their designs accordingly. For example, when participants could not be randomized across classrooms due to school structure policy and scheduling conflicts, the authors instead assigned clusters of classrooms to an experimental or control condition (Awotidebe et al, 2014;Fuller et al, 2010Fuller et al, , 2011Fuller et al, , 2015. This flexibility in study design is critical given the nature of field research.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…Although the authors of several studies acknowledged this as a limitation, they explained that randomizing participants was not always logistically possible and adjusted their designs accordingly. For example, when participants could not be randomized across classrooms due to school structure policy and scheduling conflicts, the authors instead assigned clusters of classrooms to an experimental or control condition (Awotidebe et al, 2014;Fuller et al, 2010Fuller et al, , 2011Fuller et al, , 2015. This flexibility in study design is critical given the nature of field research.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…The programme was first introduced in Africa in 2009 and has now been implemented in a total of 23 countries in Africa, Latin America, the Caribbean, South-east Asia and Oceania. The implementations are routinely monitored to assess the impact of the programme on children's health knowledge, 1 and it has been shown that the programme is effective in increasing health knowledge in Africa, [2][3][4] Mexico 5 and Brazil. 6 However, the effects of the programme on the children's health profile and physical fitness have so far not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Although such programs have not been fully implemented in many schools, they have the potential of promoting a lifestyle that values regular physical exercises from the grassroots. Similarly, rolling out previous football-based education projects like that of FIFA 11 to more schools across Malawi while delivering key messages on key modifiable risk factors for NCDs would be a key step in increasing awareness of NCDs and enhancing participation in physical activity [1,10].…”
Section: Leveraging the Power Of Footballmentioning
confidence: 99%
“…Few initiatives have been implemented tapping into the power of football in addressing NCDs in Malawi. For example, in 2007, Malawi was among the first 5 countries in Africa where FIFA implemented a pilot project called FIFA 11 for Health which is a football‐based health education initiative aimed at increasing physical activities in children while delivering 11 simple health promotion messages to improve their health knowledge and awareness of disease prevention [10]. The program was implemented in a selected few schools and the results showed that it improved the health knowledge of communicable and NCDs among learners and increased participation and engagement in physical activity [10].…”
Section: Leveraging the Power Of Footballmentioning
confidence: 99%